Navigating Dichotomies and Dilemmas; Comment on "Dual Agency in Hospitals: What Strategies Do Managers and Physicians Apply to Reconcile Dilemmas Between Clinical and Economic Considerations?" - Stephen Sirris (Kerman University of Medical Sciences, 2022)
The complexity within healthcare typically surfaces in tensions between organizational efficiency and professional values when hospital managers and professionals face dilemmas between economic and clinical considerations. Waitzberg et al, based on interviews with managers and physicians working in Israeli and German hospitals, explore strategies to cope with such dilemmas to safeguard both financial sustainability and patient quality. This short commentary provides some follow-up questions in two ways. First, I highlight the importance of nuancing and hybridizing the dichotomies that lead to dilemmas in the hospital context. Second, I discuss how such dilemmas can be highlighted in systematic group reflection which in turn can inform decision-making.